Pengembangan E-Modul Kalkulus Berbasis SETS Terintegrasi Nilai Keislaman Untuk Mahasiswa Program Studi Tadris Matematika - wahyuni, fina tri (Penerbit Widina, Widina Media Utama, 2022)
The aim of this research is to develop a SETS-based Calculus e-module integrated with Islamic values for students of the Tadris Mathematics study program and to assess its validity and practicality. The research method employed is Research and Development (RD) using a 4-stage development model: defining (Define), planning (Design), developing (Develop), and disseminating (Disseminate). Data for the study was collected using a questionnaire instrument, with the test subjects being second-semester students from the Tadris Mathematics program at the Faculty of Tarbiyah, IAIN Kudus. Data analysis involved testing the validity of expert questionnaires and evaluating the practicality of the product. The results indicated: (1) Define—problem identification revealed that students still struggle to understand the teaching materials, which are in the form of printed books, and the methods applied in online lectures. Additionally, Islamic values are not integrated into the teaching materials. (2) Design—product designs were prepared, resulting in SETS-based Calculus e-modules integrated with Islamic values using the Flip Builder application. (3) Develop—product validation by material experts resulted in a score of 3.52, classified as